MARKETING STRATEGIES IN INCREASING SALES VOLUME OF HOUSING PRODUCTS (STUDY AT PT PILAR KSATRIA TIDAR NUSANTARA KOTA SUKABUMI) - Cindy Suherti Suarsa; Erry Sunarya; Darmo H Suwiryo; Munandi Saleh (Lafadz Jaya Publisher, 2023)
This study aims to determine and explain marketing strategies for increasing the sales volume of housing products of PT Pilar Ksatria Tidar Nusantara Kota Sukabumi related to strategy planning, strategy implementation, and inhibiting factors in implementing marketing strategies. The phenomenon that occurs is a decrease in sales volume caused by the lack of appropriate marketing strategies applied. The data collection techniques are carried out through observation, interviews, documentation, and FGD. The research location is focused on PT Pilar Ksatria Tidar Nusantara Kota Sukabumi. The informants in this study were the President Director, Marketing Director, Managing Director, Finance Director, Logistics Manager, Managing Manager, and supervisory manager of PT Pilar Ksatria Tidar Nusantara Kota Sukabumi as many as 7 people. Data analysis is carried out by selecting answers obtained from informants and then collecting them for analysis and conclusions. The data analysis used is data triangulation. The results showed, that: (1) in making marketing strategy planning has involved expert consultants, but not done with a SWOT analysis approach; (2) in the implementation of marketing strategies have used the 4P approach (Product, Price, Place, and Promotion). By utilizing the advantages of products and prices that are relatively more affordable for the lower middle class. In promotional activities, there are still obstacles in facing competitors who are bolder in promotions and giving discounts. The sales volume in 2021 was 79 housing units, while in 2022 house sales were only 12 housing units or 17.5% of 2021. The contribution of this research is to expand the literature related to marketing management, especially marketing strategies to increase sales.